2019
DOI: 10.1113/ep087773
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease is associated with increased gut‐to‐blood penetration of short‐chain fatty acids: A new, non‐invasive marker of a functional intestinal lesion

Abstract: New Findings What is the central question of this study?‘Leaky gut’ has been found in intestinal and extra‐intestinal diseases. However, functional evaluation of intestinal permeability is not widely used as a diagnostic marker, possibly owing to significant limitations of currently used permeability assays. There is an unmet need for development of a new, non‐invasive test to assess intestinal function. What is the main finding and its importance?We show that an increased blood‐to‐stool ratio of the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…Many studies have confirmed that SCFAs are involved in the pathophysiology of IBD and may be a prognostic marker of the disease state [ 76 ]. Jaworska et al [ 76 ] demonstrated that compared with healthy individuals, the ratio of acids in serum to acids in feces (acetate, valerate, isocaproic, caproic and propionic acids) is statistically significantly higher in patients with IBD. These data indicate that SCFAs may be involved in the disturbance of the intestinal barrier function [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed that SCFAs are involved in the pathophysiology of IBD and may be a prognostic marker of the disease state [ 76 ]. Jaworska et al [ 76 ] demonstrated that compared with healthy individuals, the ratio of acids in serum to acids in feces (acetate, valerate, isocaproic, caproic and propionic acids) is statistically significantly higher in patients with IBD. These data indicate that SCFAs may be involved in the disturbance of the intestinal barrier function [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jaworska et al [ 76 ] demonstrated that compared with healthy individuals, the ratio of acids in serum to acids in feces (acetate, valerate, isocaproic, caproic and propionic acids) is statistically significantly higher in patients with IBD. These data indicate that SCFAs may be involved in the disturbance of the intestinal barrier function [ 76 ]. The research by Huda-Jaujan et al [ 38 ] also confirmed the role of SCFAs in the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jaworska et al [58] showed that the amount of SCFA in plasma is due not only to how much the bacteria produce, but also to intestinal permeability. Its increase can be a symptom of intestinal malfunction, which is characteristic not only of diabetes mellitus, obesity and hypertension, but also of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is based on the following findings: First, the SHHF had the same concentration of TMA in the colon content (which excludes differences in bacterial production of TMA) but a significantly higher level of TMA in the plasma. Hence, in comparison to WKY, SHHF showed a significantly higher blood-to-stool ratio of the bacterial metabolite concentration, a marker of gut–blood barrier permeability [ 15 ]. Second, the SHHF showed significant structural and functional disturbances in the intestinal wall in the form of reduced intestinal blood flow, decreased thickness of the colonic mucosa and disturbances in tight junction (TJ) proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present study, to establish the permeability of the gut to TMA in the present study, we used an indirect method; i.e., we calculated a systemic blood-to-stool ratio of the concentration of TMA. The latter method was previously validated in our lab for other gut microbiota products [ 15 ].…”
Section: Discussionmentioning
confidence: 99%